(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study aimed to evaluate the level of smart agriculture industry management in a large-scale agricultural extension system project in Udon Thani province, Thailand. The study used a mixed-methods research design, combining both quantitative and qualitative data collection methods. The data were collected from 300 farmers using a questionnaire, and 20 key informants were interviewed. The study found that the level of smart agriculture industry management was at a high level, indicating the project’s success in implementing and promoting intelligent agriculture practices among farmers. Factors that influenced smart agriculture industry management included government policy, inputs, automatic technology, and production process. The study also found that the project had a positive impact on sustainable agriculture, increasing the quantity and quality of produce. However, some limitations, such as the small sample size and the study’s geographical focus, were noted. Further research is needed to examine the factors that influence smart agriculture industry management in other regions and countries.